Certification of a Rural Endometriosis Clinic Leads to Improvement in the Diagnosis and Treatment of Endometriosis – a Retrospective Analysis - Kohl, Cynthia; Kager, Jana; Donutiu, Raul; Gerken, Michael; Papathemelis, Thomas (Geburtshilfe und Frauenheilkunde, 2025)
Endometriosis is a very common benign condition in women. In recent years certification of health care institutions has led to a more standardized care for endometriosis patients, aiming at improving the quality of diagnosis and treatment. The introduction of a common classification system facilitates quantification of disease extent. This study investigated whether certification of a rural endometriosis clinic ameliorated care in endometriosis patients.A single-center retrospective data analysis was performed of all endometriosis patients that underwent surgery at the investigated institution, certified in 2019, for the years 2018–2022.Between 2018 and 2022, a total of 812 surgeries were performed, with certification significantly improving diagnostic and surgical outcomes. Post-certification, there was an increase in ultrasound utilization (47.7% vs. 35.6%, p = 0.007), greater recognition of adenomyosis (65.8% vs. 57.0%, p = 0.035), and higher rates of complete lesion removal (92.5% vs. 87.8%, p = 0.011). Pain outcomes also improved, with more patients achieving pain relief 12 months postoperatively (40.5% vs. 34.5%, p = 0.196 vs. < 0.001). Additionally, certification enhanced follow-up assessments (64.1% vs. 40.7%, p < 0.001) and documentation of rectal lesions in patients with dyschezia (p < 0.001), indicating a positive impact on overall care quality.This study shows that certification significantly improved care for endometriosis patients. Certification enhanced diagnostic precision, increased the use of ultrasound, improved surgical outcomes, and enabled more nuanced application of the #Enzian scoring system. Follow-up assessments became more consistent, reflecting stronger quality control. Despite remaining challenges, certification elevated the clinic’s standard of care and emphasized patient-centered management.
Keywords: endometriosis; endometriosis certification; endometriosis outcome; EuroEndoCert; EuroEndoCert Certification